Ultrasound-guided transhepatic computed tomography cholecystography in beagle dogs - Kim, Dongeun (J Vet Sci, 2019)
This study was performed to evaluate the feasibility of ultrasound-guided computed tomography (CT) cholecystography and to establish an optimal protocol. In 8 healthy beagles, CT cholecystography was conducted using four contrast formulas; two dilution ratios (1:1 vs. 1:3) and two total volumes (8 mL vs. 16 mL) of 300 mgI/kg iohexol after ultrasound-guided percutaneous contrast injection into the gallbladder. CT images were obtained at 3, 10, and 30 min after injection and assessed qualitatively and quantitatively. For all contrast formulas, CT cholecystography showed the gallbladder and the intra- and extrahepatic bile ducts. The volume of the gallbladder and size of bile duct were significantly larger when using a volume of 16 mL iohexol than an 8 mL volume regardless of the dilution ratio. The distinction between the common bile duct and duodenum, the filling of the gallbladder, and the patency of bile duct were effectively assessed using a 16 mL volume of contrast agent with either dilution ratio. Beam-hardening artifacts deteriorated CT image quality for visualizing the biliary system when using the dilution ratio of 1:1. Patency of the bile tract could be easily evaluated using a curvilinear planar reconstruction. There was no significant difference in CT scan time among the different conditions. Minor leakage of contrast agent temporarily occurred after contrast injection in 30% of 32 sets of CT cholecystography. Ultrasound-guided percutaneous cholecystography can visualize both gallbladder and biliary tract with minimal artifacts using a contrast agent volume of 16 mL with a 1:3 dilution ratio.